Dirk Pitt : The Devil's Sea - Book 26 - Cussler, Dirk; Cussler, Clive (New York : G. P. Putnam's Sons, 2021)
"Fearless adventurer Dirk Pitt must unravel a historical mystery of epic importance in the latest novel in the beloved New York Times bestselling series created by the "grand master of adventure" Clive Cussler"--
Keywords: Pitt, Dirk -- (Fictitious character) -- Fiction; Pitt, Dirk -- (Fictitious character) -- Fiction; Hijacking of ships -- Fiction; Thrillers (Fiction); Suspense fiction; Suspense fiction; Action and adventure fiction; Suspense fiction